Synanthropic flora near the medieval Castle Kolno, Stare Kolnie, SW Poland - Kosina, Romuald; Marek, Lech (Biodiversity: Research and Conservation, 2023)
The medieval Castle Kolno, situated near the village of Stare Kolnie, served as a custom house at the confluence of the rivers Budkowiczanka and Stobrawa. Numerous diaspores of plants were found in archaeological excavations, in the layers of the 14th-15th centuries AD. The excavations were located near the former access road, where increased human activity has affected the composition of the fossil macroremains of plants. Two Brassica species (cabbage B. oleracea and black mustard B. nigra) cultivated in small fields near the castle were recognised. Diaspores of weeds and ruderal plants were also deposited at the site. The most frequent were: Solanum nigrum, Setaria pumila, Chenopodium album, Rumex acetosella, Persicaria lapathifolia, and Urtica dioica. The collected set of fossil diaspores is composed of plant species associated with anthropogenic habitats and shows the dispersal dynamics in various micro-niches within them.